ECOLOGICAL AND ORGANIZATIONAL ASPECTS OF RENTALS OF AGRICULTURAL LAND IN UKRAINE - Kozlova, Tetiana; Syvyck, Darya (Proceedings of National Aviation University (archive), 2015)
The aticle deals with recological and organizational problems of agricultural land lease. It is noted that under the situation of absence of proper land market the leasing relations have taken the dominant position in Ukrainian agriculture. It is determined that development of leasing relations of land should be concentrated on a competitive rental environment, the optimal level of rent forms of payment, terms of the lease and management of land leasing relations. The set of priorities of the state policy of agricultural land lease is worked out. On the base of the realized analysis the following proposals have been formulated: to strength the legislation control of the use of land leasing, to establish the environmental audit of agricultural land usage in order to minimize negative impacts on land, to develop the effective mechanisms for sustainable land use, to introduce mandatory agrochemical examination of soil before and after renting land, to introduce the appropriate incentives for owners and users in order to improve the quality characteristics of soils.